Serum insluin-like growth factor-I (IGF-I) and IGF binding protein (BP) -1, -3 adaptations to training - Hickson, R. C.; Koziris, L. P.; Chatterton, R. T.; Groseth, R. T.; Christie, J. M.; Unterman, T. G. (Medicine & Science in Sports & Exercise, 1998)
This study examined resting levels of serum IGF-I and IGFBP-1 and IGFBP-3 in competitive collegiate swimmers (M = 20; F = 9) at several time points (T1-pretraining, T2-after two months, T3-after four months (pre-taper), and T4-end of season).